Can, a putative oncogene associated with myeloid leukemogenesis, may be activated by fusion of its 3' half to different genes: characterization of the set gene. - von Lindern, M (1992)
The translocation (6;9)(p23;q34) in acute nonlymphocytic leukemia results in the formation of a highly consistent dek-can fusion gene. Translocation breakpoints invariably occur in single introns of dek and can, which were named icb-6 and icb-9, respectively. In a case of acute undifferentiated leukemia, a breakpoint was detected in icb-9 of can, whereas no breakpoint could be detected in dek. Genomic and cDNA cloning showed that instead of dek, a different gene was fused to can, which was named set. set encodes transcripts of 2.0 and 2.7 kb that result from the use of alternative polyadenylation sites. Both transcripts contain the open reading frame for a putative SET protein with a predicted molecular mass of 32 kDa. The set-can fusion gene is transcribed into a 5-kb transcript that contains a single open reading frame predicting a 155-kDa chimeric SET-CAN protein. The SET sequence shows homology with the yeast nucleosome assembly protein NAP-I. The only common sequence motif of SET and DEK proteins is an acidic region. SET has a long acidic tail, of which a large part is present in the predicted SET-CAN fusion protein. The set gene is located on chromosome 9q34, centromeric of c-abl. Since a dek-can fusion gene is present in t(6;9) acute myeloid leukemia and a set-can fusion gene was found in a case of acute undifferentiated leukemia, we assume that can may function as an oncogene activated by fusion of its 3' part to dek, set, or perhaps other genes.